Ruin probability analysis in geometric inhomogeneous claims case - Bieliauskienė, Eugenija (Lietuvos matematikos rinkinys, 2011)
The discrete time risk model with inhomogeneous claims is analyzed. The finite time ruin probability expression is obtained for the case when claims are distributed by geometric distribution with changing parameters. Some quantitave examples are also given.
Keywords: discrete time risk model; finite time ruin probability; inhomogeneous claims; geometric distribution